2020
DOI: 10.2217/cer-2019-0165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of catheter ablation devices in the treatment of atrial fibrillation: a network meta-analysis

Abstract: Atrial fibrillation (AF) ablation is most commonly performed using radiofrequency (RF) and cryoballoon (CB) catheters. Ablation Index is a novel lesion-quality marker associated with improved outcomes in RF ablation. Due to lack of direct comparative evidence between the latest generations of technologies, there is uncertainty regarding the best treatment option. Aim: To conduct a network meta-analysis to evaluate the comparative effectiveness of RF with Ablation Index to other catheter ablation devices in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Acute procedural success was also similar between the two groups in our study, with 10 out of 17 studies included in our analysis, not requiring additional RFA touch up to achieve PVI. In the network meta‐analysis by Gupta et al, contact force RFA guided by ablation index demonstrated higher freedom from arrhythmia compared with other modalities of RFA and CBA 35 . However, these results are limited by lack of direct comparison studies between CBA‐2G and RFA‐CF as well as the inclusion of several poor‐quality studies in the network meta‐analysis 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute procedural success was also similar between the two groups in our study, with 10 out of 17 studies included in our analysis, not requiring additional RFA touch up to achieve PVI. In the network meta‐analysis by Gupta et al, contact force RFA guided by ablation index demonstrated higher freedom from arrhythmia compared with other modalities of RFA and CBA 35 . However, these results are limited by lack of direct comparison studies between CBA‐2G and RFA‐CF as well as the inclusion of several poor‐quality studies in the network meta‐analysis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In the network meta-analysis by Gupta et al, contact force RFA guided by ablation index demonstrated higher freedom from arrhythmia compared with other modalities of RFA and CBA. 35 However, these results are limited by lack of direct comparison studies between CBA-2G and RFA-CF as well as the inclusion of several poor-quality studies in the network meta-analysis. 35 Our analysis is also the largest study to demonstrate that CBA-2G is equally efficacious as RFA-CF for first-time catheter ablation of patients with persistent AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data, consistent with previous studies, did not detect strong evidence of superiority with regards to efficacy in one technology over the other [ 29 , 33 , 34 ]. However, a recent NMA by Gupta et al [ 14 ] showed that PVI using RF combined with ablation index technology was superior in terms of efficacy compared with other options, such as CBA. This result is in contrast with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Network meta-analysis (NMA) is a statistical method that provides estimates of the relative effects for all available interventions, allowing comparison between every pair of treatments, even when they have not been compared directly in any trial [ 10 , 11 ]. NMA is an established method and has been applied in the field of cardiovascular medicine [ 12 , 13 ] and provides a powerful tool for the development of decision-making guidelines at different levels [ 14 ]. Thus, by employing the NMA methodology, we sought to compare the efficacy and safety of different CA strategies for the treatment of PAF.…”
Section: Introductionmentioning
confidence: 99%